2014
DOI: 10.3390/risks2020132
|View full text |Cite
|
Sign up to set email alerts
|

Effectively Tackling Reinsurance Problems by Using Evolutionary and Swarm Intelligence Algorithms

Abstract: This paper is focused on solving different hard optimization problems that arise in the field of insurance and, more specifically, in reinsurance problems. In this area, the complexity of the models and assumptions considered in the definition of the reinsurance rules and conditions produces hard black-box optimization problems (problems in which the objective function does not have an algebraic expression, but it is the output of a system (usually a computer program)), which must be solved in order to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Much of the research into the application of high‐performance computing techniques to simulations in the area of risk, specifically the insurance and reinsurance domain, has been conducted in an industrial setting and not published in the scientific literature for competitive reasons. However, this situation is slowly changing with recent papers on parallel catastrophe modelling , risk treaty optimisation and parallel reinsurance risk analytics .…”
Section: Related Workmentioning
confidence: 99%
“…Much of the research into the application of high‐performance computing techniques to simulations in the area of risk, specifically the insurance and reinsurance domain, has been conducted in an industrial setting and not published in the scientific literature for competitive reasons. However, this situation is slowly changing with recent papers on parallel catastrophe modelling , risk treaty optimisation and parallel reinsurance risk analytics .…”
Section: Related Workmentioning
confidence: 99%
“…In the actuarial context, the study conducted in [24] represents a first attempt to analyze and compare the capabilities of genetic programming and the particle swarm algorithm to find optimal solutions with respect to inspection algorithms for reinsurance problems (see also [25] for a precise definition). They concluded that the evolutionary algorithms are excellent options to find good solutions in short computation times.…”
Section: Introductionmentioning
confidence: 99%
“…In [34] and [37], they find the parameters of the reinsurance contract that maximize the joint survival probability, when the premiums of the insurer and the reinsurer are fixed, for an excess of loss risk model when the number of claims follows a Poisson process. Salcedo-Sanz et al [41] solve also this question using evolutionary and swarm intelligence techniques. In [37] the previous analysis is extended to include an optimal split of the premium income between the insurer and the reinsurer, given fixed retention and limiting levels.…”
Section: Introductionmentioning
confidence: 99%
“…Van Wouwe et al [47] determine the optimal level of excess-loss reinsurance in the case that the ultimate ruin probability is taken as stability criterion. The insurer's survival probability is also considered in [40] and [29], and more recently in [43], [44], [25], [39], [13] and [41]. Guerra and Centeno [28] obtain an optimal reinsurance policy by maximizing the insurer's expected utility.…”
Section: Introductionmentioning
confidence: 99%